Effect of Two-stage Palatal Closure to the Maxillary Growth in Complete Bilateral Cleft Lip and Palate - Yakushiji, Noboru; Wada, Takeshi; Matsuya, Tokuzo; Tachimura, Takashi; Nishio, Juntaro (Journal of Japanese Cleft Palate Association, 1987)
In order to clarify the effect of palate surgery on the maxillary growth in complete bilateral cleft lip and palate, maxillary growth with two-stage palatal closure, by our own method based on Perko' s technique, was compared to those with mucoperiosteal palatal pushback operation. After lip repair by Manchester's at age 5 months, one group (Bil-T Group) of patients received two-stage palatal closure which include primary veloplasty at age 20 months and hard palate closure at age 5 year 10 months. Another group (Bil-S Group)received mucoperiosteal palatal pus hback operation at 20 months. A longitudinal and three-dimensional maxillary growth was monitored by the measurement of maxillofacial models obtained from each patient. Non-cleft subjects were classified as a control group to match the cleft groups by age and by body age. The results showed that t here was no maxillary growth difference between the Bil-T group and the Bil -S group in any dimensions studied, and that the growth inhibition in height of the maxilla of both Bil-T a nd Bil-S groups became more remarkable compared to the control group after lip and palatal surgery. These results may indicate that careful consideration is needed for the choice of two-stage p alatal clousre in cases with complete bilateral cleft lip and palate.